The Fruits of the Boom: Real Wages and Housing Costs in Dakar, Senegal (1914-1960) - Tom Westland (African Economic History Network (AEHN), 2021)
The incomes of unskilled workers in Dakar under colonial rule was comparable to those of their counterparts elsewhere in West Africa. Real urban wages grew during the Great Depression and the 'Ëœdevelopmental decade' following World War II, though accounting properly for housing costs results in substantial downward revision to both the level and growth of real wages. This paper argues that a similar revision is likely necessary for real wage estimates in other colonies in Africa. The magnitude of this correction suggests that much of the fruits of the economic boom of the first half of the twentieth century were 'Ëœsoaked up' by urban landlords, pointing to an important driver of inequality in urban colonial Africa.
Keywords: N17; N37; N57; 330; Africa; Senegal; Real Wages; Housing Costs